2009
DOI: 10.1128/jb.00861-09
|View full text |Cite
|
Sign up to set email alerts
|

Motility and Flagellar Glycosylation in Clostridium difficile

Abstract: In this study, intact flagellin proteins were purified from strains of Clostridium difficile and analyzed using quadrupole time of flight and linear ion trap mass spectrometers. Top-down studies showed the flagellin proteins to have a mass greater than that predicted from the corresponding gene sequence. These top-down studies revealed marker ions characteristic of glycan modifications. Additionally, diversity in the observed masses of glycan modifications was seen between strains. Electron transfer dissociati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
167
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(173 citation statements)
references
References 36 publications
(46 reference statements)
6
167
0
Order By: Relevance
“…Some systems display robust inter-and intrastrain glycan variability, suggesting that glycoform diversification is adaptive. For example, flagellar protein glycosylation systems in Campylobacter jejuni and Clostridium species display remarkable plasticity in glycoform expression (2)(3)(4). However, precise correlations between glycosylation gene content and glycoform phenotypes have been difficult to establish.…”
mentioning
confidence: 99%
“…Some systems display robust inter-and intrastrain glycan variability, suggesting that glycoform diversification is adaptive. For example, flagellar protein glycosylation systems in Campylobacter jejuni and Clostridium species display remarkable plasticity in glycoform expression (2)(3)(4). However, precise correlations between glycosylation gene content and glycoform phenotypes have been difficult to establish.…”
mentioning
confidence: 99%
“…This mechanism has long been considered to be restricted to O-glycosylation like in Campylobacter, Helicobacter, or Pseudomonas spp. for flagellar proteins (12)(13)(14)(15). However, it was recently demonstrated that HMW1c, a GT of Haemophilus influenzae, was responsible for the cytoplasmic N-glycosylation of the adhesin HMW1 (16,17).…”
mentioning
confidence: 99%
“…GmaR was the first prokaryotic enzyme of this type to be characterized (20). The type of sugar added to flagellins and the number of modified sites is different between species and is even straindependent in Clostridium difficile (13). Genomic analysis suggests that flagellin glycosylation in Clostridium spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, cytosolic Leloir (nucleotide-dependent) glycosyltransferases transfer the sugars from nucleotide-activated donors to the protein acceptors. For example, bacterial species such as Clostridium difficile, Haemophilus influenzae, and Helicobacter pylori glycosylate adhesins and flagellins using specialized N-and O-glycosyltransferases in the bacterial cytoplasm (2)(3)(4). Alternatively, glycosylation may occur via an en bloc mechanism, in which the sugars are assembled onto a lipid carrier before being transferred to acceptor proteins through the activity of specialized non-Leloir glycosyltransferases collectively known as "oligosaccharyltransferases" (OTases).…”
mentioning
confidence: 99%